A Constructivist Instructional Model for the Implementation of Thariqah Mubasyarah in Beginner Mufrodat Instruction - Alfiansyah Alfiansyah; Fattah Khoirun; Ngantori Ngantori; Afriana Santosa (JURNAL ISLAM NUSANTARA, 2025)
This study aims to examine the relationship between constructivist theory and the application of thariqah mubasyarah in beginner-level mufrodat learning, emphasizing its urgency in fostering meaningful vocabulary acquisition. Despite the centrality of Arabic in pesantren education, traditional rote memorization methods dominate, resulting in passive learning that limits students’ ability to internalize and apply vocabulary effectively. Constructivist approaches highlight active engagement, social interaction, and contextualized learning as key mechanisms for constructing knowledge. This research employed a qualitative descriptive design to explore how constructivist principles underpin the implementation of thariqah mubasyarah in beginner-level mufrodat lessons. The findings reveal three major outcomes: first, students’ activeness increased through direct interaction with objects, verbal participation, and sensory engagement, transforming rote memorization into meaningful learning. Second, social interaction and collaboration in pairs or groups facilitated peer scaffolding, enhancing vocabulary retention, communicative confidence, and cooperative learning. Third, independence and creativity emerged as students designed dialogues, performed role-plays, and applied vocabulary in authentic contexts, reflecting self-directed construction of knowledge. The study contributes to Arabic language education by providing empirical evidence that thariqah mubasyarah grounded in constructivist theory promotes active, collaborative, and creative learning. It is recommended that educators integrate constructivist principles in curriculum design to enhance vocabulary mastery, critical thinking, and communicative competence.